2018
DOI: 10.7150/jca.26008
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer and Pulmonary Embolism: What Is the Relationship? A Review

Abstract: Pulmonary embolism (PE) is gradually considered to be the third most common disease in the vascular disease category. Lung cancer is the most frequently diagnosed cancer and the leading cause of cancer death among males worldwide. Although initially appearing as distinct entities, lung cancer is a great risk factor for the development of PE. Pulmonary embolism is common in lung cancer patients, with a pooled incidence of 3.7%, and unsuspected pulmonary embolism (UPE) is also non-negligible with a rough rate ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 89 publications
4
25
0
Order By: Relevance
“…In the study, there were 29 lung adenocarcinoma patients both in the case and control groups by coincidence, but some individuals had not performed gene detection owing to different reasons. Final statistical results showed that EML4/ALK rearrangements between the case and control groups had no statistical difference (8.7% vs 4%, P > 0.05), which was not consistent with some previously published literature 9,13 . The frequency of EGFR mutations in PE group was close to that in non‐PE group (43.5% vs 56%, P > 0.05) and it has been reported similarly in the past 13 (Table 4).…”
Section: Resultsmentioning
confidence: 48%
“…In the study, there were 29 lung adenocarcinoma patients both in the case and control groups by coincidence, but some individuals had not performed gene detection owing to different reasons. Final statistical results showed that EML4/ALK rearrangements between the case and control groups had no statistical difference (8.7% vs 4%, P > 0.05), which was not consistent with some previously published literature 9,13 . The frequency of EGFR mutations in PE group was close to that in non‐PE group (43.5% vs 56%, P > 0.05) and it has been reported similarly in the past 13 (Table 4).…”
Section: Resultsmentioning
confidence: 48%
“…Pulmonary embolism represents a pooled incidence of 3.7% in lung cancer patients [ 19 ]. In COSTECAT study more than half of patients (55.3%) had PE.…”
Section: Discussionmentioning
confidence: 99%
“…First, the patient initially presented with PTE, and it is generally recognized that cancer has a high risk of PTE. Li et al reported that pulmonary embolism (PE) is a frequent finding, with an overall incidence of 3.7% (1,172 of 31,294), ranging from 0–23.7% in lung cancer patients ( 9 ). PE resulted from a combination of the following: vascular endothelial damage, stasis of blood flow, and hypercoagulability.…”
Section: Discussionmentioning
confidence: 99%